2018
DOI: 10.1002/ppul.24018
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a health‐related quality of life questionnaire for pediatric patients with interstitial lung disease

Abstract: The results indicate the reliability and validity of the chILD-QoL for pediatric patients with interstitial lung diseases. It can be used for screening and monitoring subjective health status as perceived by the patients and/or their caregivers, as well as for evaluation of health-related quality of life in clinical trials and intervention research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 33 publications
3
27
1
1
Order By: Relevance
“…In this study, the high response rate (88%) of children over 8 years old confirmed their great interest in taking part in the assessment of their condition. The overall response rate (70%) is comparable with other QoL studies . The main finding of this study is the confirmation that HR‐QoL is significantly impaired in chILD.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In this study, the high response rate (88%) of children over 8 years old confirmed their great interest in taking part in the assessment of their condition. The overall response rate (70%) is comparable with other QoL studies . The main finding of this study is the confirmation that HR‐QoL is significantly impaired in chILD.…”
Section: Discussionsupporting
confidence: 86%
“…HR‐QoL questionnaires should also be more widely used as a health outcome in clinical trials. For chILD, Niemitz et al recently proposed a modified QoL questionnaire based on the Generic PedsQL with more disease‐specific items (5 to 11 questions according to the age of the child). This first chILD‐specific HR‐QoL demonstrated moderate to high correlations with the generic PedsQL, depending on the dimensions and the ages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 While early investigations focused on the etiologies, phenotypes, and natural courses of specific disease entities, chILD researchers have recognized the need to identify meaningful outcome measures to move toward interventional trials. 30 To that end, Niemitz et al 31 developed a questionnaire to assess patient-and parent-reported quality of life for chILD. Items were developed from focus groups with affected children and parents.…”
Section: Identification Of Congenital Lung Malformations (Clms) Hasmentioning
confidence: 99%